Impact of Yucca extract and basil oil supplementation on carcass characteristics, quality of meat, and the cecal microbiota in broiler chickens - Elmeligy, Eman H.; Attallah, Sanad T.; Sallam, Eman A.; Mohammed, Liza S. (Journal of Advanced Veterinary Research, 2025)
The current study investigated the effects of Yucca extract and basil oil as phytogenic supplements on broiler chickens’ carcass traits, different return parameters of carcass, quality of meat and the cecal microbes. A total of 200 one day-old avian 48 broiler birds were divided into 5 treatments. The dietary treatments were control group fed basal diet only (CON), group fed basal diet +150 mg yucca extract /kg ration (YE 150), group fed basal diet + 300 mg yucca extract /kg ration (YE 300), group fed basal diet + 400 mg basil oil /kg ration (BO 400) and group fed basal diet + 800 mg basil oil/kg ration (BO 800). Our outcomes showed that differences weren’t significant in carcass traits and different return parameters between different groups, while there were numerical increase in total return from carcass and breast meat % in all treated groups than control group. Dressing % for yucca and BO 800 groups showed numerical increase than those of control & BO 400 groups. Tenderness, malondialdehyde (MDA), total antioxidant capacity (TAC), PH and color showed significant difference. MDA decreased in BO groups and TAC increased in YE 300 and BO groups compared to control group, PH decreased in YE 150 compared to other groups. Also, using YE and BO didn’t affect total aerobic bacterial count, while had positive impact on lactobacillus count. In conclusion, including YE and BO in the diet did not negatively impact carcass traits but enhanced meat quality and lactobacillus count in broiler chickens.